Avaliação das medidas de pressão arterial na unidade de pronto atendimento e triagem do Hospital São Paulo comparadas ao Padrão-ouro - Elias e Silva, Luciano [UNIFESP] (2015)
OBJECTIVE: Evaluating arterial pressure measurements comparing the traditional and the gold standard methods in an emergency public service and risk classification. METHODS: Cross sectional study, in which arterial systolic, diastolic, mean and pulse pressure measurements obtained by nursing professionals by means of the traditional method were compared whit those obtained using the gold standard technique. RESULTS: Study participants were 229 patients, 69% were women and the mean age was 50 years. The comparison between the two methods showed that the mean value of the arterial systolic, diastolic, mean and pulse pressures was higher using the gold standard technique. CONCLUSION: Divergences were found between the measurements obtained using the recommended technique and the risk classification and the measurement results of this underestimated those obtained using the gold standard technique.